2019
DOI: 10.1097/moo.0000000000000583
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia lusoria: problem or incidentaloma?

Abstract: Purpose of review To address the incidental versus pathogenic nature of dysphagia lusoria and to provide a review of the cause, clinical presentation, diagnosis, and treatment of this condition with respect to recent literature. Recent findings Case reports comprise the majority of recent literature concerning dysphagia lusoria. Many patients with an aberrant right subclavian artery (ARSA) have additional coexisting vascular anomalies. While most indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…(3) The anatomical course of this anomalous artery can vary as it passes from the chest into the right arm. (1,4) In most cases (80%), it will cross between the esophagus and the spine.…”
Section: Discussionmentioning
confidence: 99%
“…(3) The anatomical course of this anomalous artery can vary as it passes from the chest into the right arm. (1,4) In most cases (80%), it will cross between the esophagus and the spine.…”
Section: Discussionmentioning
confidence: 99%
“…However, a more recent study showed that while 71.2% of their 141 ARSA cases reported dysphagia as a symptom, only 19.2% (27/141) possessed the bicarotid morphology [8]. In addition, in many cases of a BCT co-occurring with an ARSA, barium-contrast examination indicates that the esophagus is compressed posteriorly and obliquely at the level of the aorta [3,4,6,9,15,[18][19][20], suggesting that the ARSA is the primary contributor to esophageal compression and resulting dysphagia. There are also documented cases in which a BCT is absent or extremely mild, but dysphagia still presents [19,21].…”
Section: Coexisting Malformations Of the Aberrant Right Subclavian Armentioning
confidence: 99%
“…The ARSA variant morphology develops when the right fourth aortic arch fails to develop, which results in the right seventh intersegmental artery remaining attached to the dorsal aorta, which derives the ARSA formation [2,7,8]. In approximately 80% of cases, the ARSA takes a retroesophageal course, with an interesophageotracheal course occurring in 16.7% of cases and 5% of cases traveling anterior to the trachea [7,18].…”
Section: Embryological Origin Of the Aberrant Right Subclavian Arterymentioning
confidence: 99%
See 2 more Smart Citations